Two new tropolonic alkaloids from Colchicum speciosum Steven bulbs - S. Tayyeb*; S. Nejad Ebrahimi; M.H. Mirjalili; M. Tabefam; M. Hamburger (Iranian Society of Pharmacognosy, 2017)
Background and objectives: The genus Colchicum belongs to the family Colchicaceae, which comprises of 19 genera, and 225 species worldwide. They have been recognized for more than 2000 years for their noticeable biological properties. The Colchicum species are well known for presence of tropolonic alkaloids, mainly colchicine. Colchicine, is still the drug of choice for treatment of gout, and is used for the treatment of a number of proinflammatory disorders, such as familial Mediterranean fever, and Behcet's disease. Clinical studies have proved colchicine to posses potent anti-tumor activity. Colchicum speciosum Steven is an indigenous perennial herbaceous plant widely distributed in northern, central and western regions of Iran.  Methods: In the present study, the phytochemical composition of MeOH extract from bulbs of C. speciosum collected fromSavadkouh region, Iranwas investigated by combination of HPLC-PDA-MS spectrometry and NMR specroscopy. The fractionation of MeOH extract was carried out by partitioning on CH2Cl2, EtOAc and water. Results: The isolation and purification of CH2Cl2 portion by combination of reverse and normal phase chromatography resulted in the isolation, purification and identification of two new tropolonic alkaloids, compounds (1) and (2), as well as two known compound colchicine (3) and demecolcine (4). Their structures were established by extensive spectroscopic methods, including 1D (1H NMR) and 2D-NMR (COSY, HSQC and HMBC). The absolute configurations of isolated compounds were established by aid of circular dichroism. Conclusion: Phytochemical investigation of CH2Cl2 extract of C. speciosum by combination of HPLC, column chromatography and hyphenated spectroscopic techniques led to identification two new alkaloids with potential as lead compounds.